The The Effectivity of Palm Oil Kernel Shell (OPS-Fe3O4) for Phenol Waste Degradation Routes - Adrianto, Ari; Hadi Pratomo, Bagus; Cahya Pratiwi, Dwita; Rahmawati, Evi (Al-Kimia, 2023)
Phenol is a type of hazardous waste that can irritate skin, eyes, and mucous membranes in humans. It has been discovered that the phenol content in wastewater generally ranges from 1-6800 ppm. Phenol removal applications such as adsorption separation are highly recommended, one of which is the application of activated carbon. Activated carbon can be produced from natural biomass which has a high content of lignin, carbon, and hemicellulose. One of the most developed biomass is OPS (Palm Oil Kernel Shell). OPS’ texture is a hard textured endocarp and dark gray. To increase waste degradation, the application of magnetite (Fe3O4) was found to be an effective modification of the adsorbent. In the experimental results, variations in adsorbent dosage, particle size, and contact time were carried out. At various adsorbent doses, the addition of 1g/ml was more effective in producing up to 98.5% removal. Meanwhile, the size of 0.05 mm produces highest degradation when compared to 0.22 mm and 0.55 mm. The optimum contact time reveals that it occurs in the range of 50-60 minutes. The FTIR results revealed that the most abundant O-H, C=C and N-H content was found to be adsorbed at each particle size.